Hybrid CMOS single-electron-transistor device and circuit design - Mahapatra, Santanu (Artech House integrated microsystems series., 2006)
"This cutting-edge resource shows engineers how to take advantage of the low-power consumption and enhanced functionality of SETs (single-electron transistors) along with the high-speed driving and voltage gain of CMOS technology. The book provides the conceptual framework for CMOS-SET hybrid circuit design. Supported with over 180 illustrations and packaged with a CD-ROM of practical supplementary material, the book discusses."--Jacket